WTO agreements & public health : a joint study by the WHO and the WTO Secretariat. (Nonserial Publication., 2002)
This report deals with the relevant WTO Agreements and the way they may influence health and health policies. At the national level, health policy makers are increasingly interested in the two-way connection between trade and health. The principle objective of this report is to describe the actual and potential linkages between relevant WTO agreements and health so as to enable both trade and health officials to better understand, and monitor the effects of, these linkages. The report examines the main WTO Agreements to health and health policies namely the Agreements on Technical Barriers to.